2022
DOI: 10.14444/8383
|View full text |Cite
|
Sign up to set email alerts
|

The H Laminectomy: Technical Description and Clinical Experience From the First 85 Patients

Abstract: Background: Over the years, lumbar laminectomy has been widely employed by spinal surgeons for many purposes throughout the spinal canal. The Misonix BoneScalpel relies on ultrasonic energy and allows the surgeon to make precise osteotomies while protecting collateral or adjacent soft tissue structures. Amplification of electric impulses allows the blade in the BoneScalpel to oscillate at very high frequencies, which thus allow it to cut bone with immense amounts of heat, which are then tempered with copious i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Decompressive laminectomies are common in spine surgery, benefiting from advancements like rongeurs, high-speed drills, and ultrasonic osteotomes, which provide precision and protect soft tissues [4]. Our technique involves two vertical cuts on the lamina and two oblique cuts at the pars interarticularis, differing from the H laminectomy method [5]. The cut across the lamina in the ultrasonic H laminectomy technique to free the lamina from its bony attachments can be dangerous because the spinal cord is directly underneath without the ligamentum flavum as a buffer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decompressive laminectomies are common in spine surgery, benefiting from advancements like rongeurs, high-speed drills, and ultrasonic osteotomes, which provide precision and protect soft tissues [4]. Our technique involves two vertical cuts on the lamina and two oblique cuts at the pars interarticularis, differing from the H laminectomy method [5]. The cut across the lamina in the ultrasonic H laminectomy technique to free the lamina from its bony attachments can be dangerous because the spinal cord is directly underneath without the ligamentum flavum as a buffer.…”
Section: Discussionmentioning
confidence: 99%
“…The constant visualization and tactile feedback of the tip of the instrument and osteotome provided an inherent safety mechanism and allowed enhanced control of the dura-ligamentum interface, even for nonexperienced surgeons. They concluded that the H laminectomy is a safe and effective way to perform a lumbar laminectomy [5].…”
Section: Introductionmentioning
confidence: 99%